Improved production technology of sisal - Sarkar, Sitangshu; Kar, C S; Sinha, M K; Mahapatra, B S (Indian Farming, 2015)
Sisal can survive drought condition but areas having evenly distributed moderate rainfall are suitable. It can be planted on a wide range of soils. However, light calcareous and gravelly soils with good drainage are suitable. Sisal is mainly propagated vegetatively through bulbils and suckers. For sisal planting, pits of 1 ft3 are recommended. Pits are filled up with mixture of soil and organic matter. Two methods of planting, viz. single row planting and double row planting are followed. Double row planting is always more profitable. Plant density depends on nature and fertility status of soil, type of farming, investment and management capacity of the grower. Some of the suitable spacing are 4 m + 1 m Ã— 1 m (4000 plants/ha) and 3 m + 1 m Ã— 1 m (5000 plants/ha). Planting are done with the onset of monsoon rain, so plants establish well. During the initial couple of years, harvesting of leaves are not recommended and sufficient space in between rows are available for intercropping of horse gram, finger millet and other small millets, blackgram etc. Hoeing and weeding are essential at least for the first three years. After each weeding, application of fertilizer is recommended @ 60:30:60 kg of N, P2O5 and K2O/ha. Harvesting of leaves is started at 3 years 6 months crop age. At first cutting 16 leaves and in each subsequent cutting 12 leaves are left on the plant. The harvested leaves are then transported to the extraction shed and extraction of fibre is done on the same day or preferably next day as early as possible by deploying raspador decorticator. The fibre is repeatedly washed in water and then spread on ropes or wires till it is sufficiently dry. In general, the average productivity of sisal in India is not more than 600 kg/ha. However, improved techniques with proper management of sisal plantation can produce 1.5 tonnes/ha. A net profit of Rs.20,000 is normally achievable from a hectare of sisal plantation